PENGARUH PEMBERIAN STIMULASI PADA KASUS INERTIA UTERI TERHADAP JENIS PERSALINAN - Yanti, Linda (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
Barriers or bottlenecks of labor may be caused because the uterus does not contract properly (inertia uteri) which is a complication of childbirth. Handling of cases of uterine inertia must be done right. Objective to analyze the effect of stimulation in cases of uterine inertia against this type of labor. This type of research used in this research is analytic observational case control approach. The population in this study were women with uterine inertia cases in hospitals Margono Soekardjo Purwokerto. The sample used was a mother with a case of uterine inertia of the 100 respondents was taken by quota sampling. The results of the bivariate analysis with chi-square there is the effect of stimulation in cases of uterine inertia with the kind of labor with (p-value = 0.001) (Tabel.1). with OR = 3.5857 which means that mechanical stimulation in cases of uterine inertia 3.5857 times higher chance of having a vaginal birth than the combined stimulation. There is significant relationship between stimulation in cases of uterine inertia with the type of delivery Keywords: Stimulation, Inertia uteri, Type of labor